Comparison of bead shape, microstructure and mechanical properties of fiber laser beam welding of 2 mm thick plates of Ti-6Al-4V alloy. (September 2018) - Kumar, Chandan; Das, Manas; Paul, C.P.; Bindra, K.S.
Highlights: Fibre laser welding of 2 mm thick plates of Ti-6Al-4V alloy is successfully conducted. Bead features, surface appearance and mechanical properties are examined as a measure weld quality. Physical interpretation of phase transformation in the fusion zone and heat affected zone are investigated. The sizes of porosities are within acceptable range. Welding conditions for T-shaped weld-bead is favorable than X-shaped bead. Abstract: Fiber laser beam welding experiments are carried out on 2 mm thick plates of Ti-6Al-4V alloy at various welding conditions. A specially designed workpiece fixture with shielding gas delivery system is fabricated and effectiveness of shielding gas is confirmed by energy dispersive X-ray spectroscopy analysis. Two different types of bead cross-sections i.e. T-shaped and nearly X-shaped beads are observed at different line energies. After experiments, width and area of fusion zone and size of heat affected zone are measured and further analyzed. The microstructural studies at different locations in heat affected zone and also in fusion zone are carried out with optical microscope and their morphologies are compared at different welding conditions using field emission scanning electron microscope. The porosities are observed in both T and X-shaped weld beads at different line energies. However, their sizes are in acceptable range as per BS EN:4678 standard. The maximum microhardness is found in fusion zone due to the presence of large amount of α′ martensite. The line energy utilization factor is higher for T-shaped bead than X-shaped bead. The tensile strength of T-shaped bead is lower than X-shaped bead due to higher non-uniformity in the distribution of plastic strain. The experimental results show that T-shaped welding conditions are favorable while considering full penetration in keyhole mode, narrower weld width and lesser heat affected zone.